2016
DOI: 10.1590/1981-52712015v40n4e00122015
|View full text |Cite
|
Sign up to set email alerts
|

Como os Egressos do Provab e Aprovados na Residência Avaliaram a Experiência?

Abstract: RESUMO Objetivos: Descrever a influência do Programa de Valorização do Profissional da atenção básica (Provab)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
(1 reference statement)
1
1
0
4
Order By: Relevance
“…In accordance with the professionals who participated in this study, the PROVAB was the first great experience in PHC in their lives, as also illustrated in a study by Lima et al with other PROVAB doctors [23]. It is clear from the findings that PHC can be a working locus desired by medical professionals when they find meaning in their actions and possibilities of transformation and improvement of care based on the close relationship and bond with users and teams.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In accordance with the professionals who participated in this study, the PROVAB was the first great experience in PHC in their lives, as also illustrated in a study by Lima et al with other PROVAB doctors [23]. It is clear from the findings that PHC can be a working locus desired by medical professionals when they find meaning in their actions and possibilities of transformation and improvement of care based on the close relationship and bond with users and teams.…”
Section: Discussionsupporting
confidence: 80%
“…We observed in the speeches that, with the lack of adequate conditions for the development of PHC, the subsidy became the main reason for staying in the program. In these situations, they tend to perpetuate the factors that led the professionals to enter the Program, discouraging them to remain in PHC, a situation also observed in another study [23, 39]. A limitation of the study was the lack of participation of all the doctors that had precedence over PROVAB to PMM, which might had affected the inclusion of other positive perceptions related to the possible advances in the formative perspective of the Program, as well as the retention of the professionals in this field, once the study suggested analyzing the factors and motivations that led doctors to take this decision.…”
Section: Discussionmentioning
confidence: 68%
“…Neste estudo, não foi observada qualquer evidência que permita inferir a utilização dos dados dos sistemas de informação do Provab para analisar indicadores de saúde e epidemiológicos da população adstrita às Equipes de Saúde da Família (EqSF) em que atuavam médicos do Provab. A análise dos dados permitiria inferências sobre o trabalho dos profissionais nos programas de provimento e das suas respectivas equipes, principalmente com relação à ampliação do acesso à saúde e ao comportamento dos indicadores de internação por causas sensíveis à atenção básica 25,27,28 .…”
Section: Discussionunclassified
“…Herzberg (1966) tinha como objetivo identificar os fatores que causavam a satisfação e a insatisfação dos empregados no ambiente de trabalho, determinando assim os Fatores Higiênicos e Fatores Motivacionais. Os fatores higiênicos são aqueles necessários para evitar que o funcionário fique insatisfeito em seu trabalho, porém, eles não são capazes de fazer com que ele se sinta completamente satisfeito.…”
Section: Teoria Dos Dois Fatores De Frederick Herzbergunclassified
“…Dentre as teorias motivacionais pesquisadas, a que traz um forte impacto ao desenvolvimento da motivação ao colaborador diante do reconhecimento profissional é a teoria desenvolvida por Frederick Herzberg (1966), a teoria dos dois fatores, fatores higiênicos e fatores motivacionais. Segundo Herzberg (1966), o que mais contribui para o crescimento na produção dos colaboradores são os fatores motivacionais. Deve-se procurar aumentar ao máximo esses fatores, pois são os principais responsáveis pela melhora dos resultados.…”
Section: A Teoria Motivacional Dos Dois Fatores E Sua Aplicaçãounclassified